Do Teachers and Students Share the Same Feedback Meaning? A Quantitative Study among Secondary Schools in Bulawayo, Zimbabwe - Muchemwa, Stella (Africa Journals Online, 2022)
Teachers’ feedback has been used for centuries by students who use English as second language to improve their writing skills. This study sought to find out the students and teachers’ responses to teacher corrective feedback in composition writing among Secondary Schools in Bulawayo, Zimbabwe using parallel questionnaires for teachers and students. The study also analyzed whether there was a significant difference between teachers and students’ responses. Fifty-six teachers and 251 ‘O Level English students randomly selected from 25 secondary schools in Bulawayo were the sample of the study. Data collected from the questionnaires was analyzed through Statistical Package for Social Sciences (SPSS version 10). Findings showed that there were high overall means for Feed Up, Feed Back and Feed Forward for both teachers and students who valued these response aspects although they disagreed on some aspects. Independent samples Mann-Whitney U test showed that there was a significant difference between the teachers’ and students’ responses on Feed Up and Feed Back, Sig =.000. It is only in Feed Forward that there was no significant difference in responses as shown by a Sig of .072. The study therefore recommended that teachers should always have mechanisms in place to find out whether the students have understood teachers’ feedback or not in order to assist learners accordingly as well as using such information on planning and developing useful teaching strategies. The schools administration should provide teachers with the necessary resources for them to be able to adequately and properly assist learners in the composition writing process.